Progressive Women's Da'wah Movement in Southeast Sulawesi, Indonesia - Alifuddin, Muhammad; Lur Rochman, Kholil; Hasanah, Uswatun; Budiantoro, Wahyu (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
This research aims to explain the pattern of the Aisyiyah Da'wah Movement in Southeast Sulawesi and how Aisyiyah's strategy manages opportunities and mobilizes her strength to realize the ideals of its da'wah movement. This research data was obtained through in-depth interviews, observation, and document review. In-depth interviews were conducted with female Muhammadiyah figures in Southeast Sulawesi. Observations were used to observe the da'wah activities female Muhammadiyah figures carried out. All data were analyzed using the Miles and Huberman paradigm. Based on the data and analysis carried out, the following conclusions were obtained: Aisyiyah's da'wah movement was carried out in two patterns, namely: (1). Da'wah in the form of tabligh, namely transmitting Islamic teachings verbally (lectures) both offline and online and through writing in the form of distributing brochures, magazines containing religious understanding from a Muhammadiyah perspective. In its implementation, tabligh in the form of recitation is mainly carried out in the internal environment. In contrast, tabligh, in the sense of the involvement of Aisyiyah figures in providing recitations in mosques and majlis taklim, has not been touched by Aisyiyah. (b) Da'wah bi al-hal, namely an approach that integrates da'wah with social and humanitarian action. The phenomenon can be seen in Aisyiyah's active involvement in tackling TB and the Covid-19 outbreak. Aisyiyah also integrates da'wah into the learning system in the schools and universities she owns. The Southeast Sulawesi Aisyiyah da'wah movement through educational institutions is quite progressive.